Coenzyme Q10 Reduces Infarct Size in Animal Models of Myocardial Ischemia-Reperfusion Injury: A Meta-Analysis and Summary of Underlying Mechanisms - Awad, Kamal; Sayed, Ahmed; Banach, Maciej (Frontiers in Cardiovascular Medicine, 2022)
Objective Effective interventions that might limit myocardial ischemia-reperfusion (I/R) injury are still lacking. Coenzyme Q10 (CoQ10) may exert cardioprotective actions that reduce myocardial I/R injury. We conducted this meta-analysis to assess the potential cardioprotective effect of CoQ10 in animal models of myocardial I/R injury. Methods We searched PubMed and Embase databases from inception to February 2022 to identify animal studies that compared the effect of CoQ10 with vehicle treatment or no treatment on myocardial infarct size in models of myocardial I/R injury. Means and standard deviations of the infarct size measurements were pooled as the weighted mean difference with 95% confidence interval (CI) using the random-effects model. Subgroup analyses were also conducted according to animals' species, models' type, and reperfusion time. Results Six animal studies (4 in vivo and 2 ex vivo) with 116 animals were included. Pooled analysis suggested that CoQ10 significantly reduced myocardial infarct size by −11.36% (95% CI: −16.82, −5.90, p < 0.0001, I2 = 94%) compared with the control group. The significance of the pooled effect estimate was maintained in rats, Hartley guinea pigs, and Yorkshire pigs. However, it became insignificant in the subgroup of rabbits −5.29% (95% CI: −27.83, 17.26; I2 = 87%). Furthermore, CoQ10 significantly reduced the myocardial infarct size regardless of model type (either in vivo or ex vivo) and reperfusion time (either ≤ 4 h or >4 h). Conclusion Coenzyme Q10 significantly decreased myocardial infarct size by 11.36% compared with the control group in animal models of myocardial I/R injury. This beneficial action was retained regardless of model type and reperfusion time.